Ogródki rozrywkowe w Poznaniu w dziewiętnastym i dwudziestym wieku - Langwińska, Anna (Studia Edukacyjne, 2025)
The main subject of this thesis is the entertainment gardens of Poznań in the 19th and 20th centuries. The author aimed to describe the most significant of them to analyze their importance and role within the cultural and social life of the city. The thesis also aimed to present the origins of entertainment gardens, their modes of operation, architectural features related to their functions, as well as the artistic and entertainment events that shaped their public image.